Effects Of Thinning On Growth And Sap Flow In Nine-Year-Old Azadirachta Excelsa (Jack) In Merlimau,Melaka, Malaysia - Koter, Rosdi (2007)

(untitled)
Since 1997, the forest plantation in Malaysia has gained further momentum with the inclusion of selected indigenous species for forest plantation development. Considering the size of plantations being established, the need for studies on silvicultural operation is widely recognized. Until now, except for Acacia mangium, there was no specific model on silviculture and maintenance of each species being planted in Malaysia. The objectives of this study were to quantify the effects of thinning regime on the diameter growth, stand volume and crown structure and to determine the effect of sap flow of thinned and unthinned A. excelsa stands. The study was conducted in the, Sime Darby Estates, Merlimau, Melaka. The A.excelsa stands were planted at an initial spacing of 3 x 4 m (833 stem ha-1) over 2 hectares in May 1995. There were two treatments used for this study; unthinned as control and moderate thinning, where 50% of the stand were felled systematic according to lines. In addition sap flow velocity of selected trees in both treatments were measured using heat pulse probe connected to data logger. During the study, the achieved mean diameter at breast height of A. excelsa was 14.30 ± 0.81 cm and the mean of the potential final crop trees (300 trees ha-1) of 18.99 ± 0.78 cm. The mean periodic annual diameter increment was 1.87 ± 0.07 cm year-1 before thinning and 1.60 ± 0.08 cm year-1 23 months after thinning. The periodical annual diameter increments are not significantly different between plots after 23 months. The diameter increment is still increasing indicating that the growth of the species has not reached the optimum rate. The response to thinning also includes the effect on the expansion of the crowns. Results presented from this trial have indicated that the thinning has a positive effect on crown development in which thinned A.excelsa stand reached up to 6.5 m in length, as compared with the unthined treatment up to 5.0 m. The crown length increment was significantly, being greater by quantify by 30% in the thinned plot. The crown radial of both unthinned and thinned stand varied from 0.2 to 3.6 m and 0.1 to 4.2 m respectively. The amount of water loss in the thinned stand was significantly higher than those in the unthinned plot, 0.53 liter/hour compared with 0.32 liter/hour respectively. The rate of water loss for A. excelsa at thinned stand was higher than those from unthinned stand with a total of 12.02 liters and 10.27 liters over day respectively. Higher soil moisture content was also observed in thinned plot compared to unthinned plot. This study provides useful information on the growth of A.excelsa due to thinning activities by creating the gap opening and the water loss implication after thinning was undertaken. Such information is useful in making long-term growth projections with growth adjusted to variation of microclimate within the stand.